2018
DOI: 10.1371/journal.pone.0204435
|View full text |Cite
|
Sign up to set email alerts
|

Afterload dependence of right ventricular myocardial deformation: A comparison between tetralogy of Fallot and atrially corrected transposition of the great arteries in adult patients

Abstract: BackgroundPrior studies suggested that myocardial deformation is superior to conventional measures for assessing ventricular function. This study aimed to evaluate right ventricular (RV) myocardial deformation in response to increased afterload. Patients with the RV in the systemic position were compared with patients with the RV in the sub-pulmonic position with normal or only slightly elevated systolic right ventricular pressure. Correlations between global longitudinal strain (GLS), radial strain, atriovent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…We observed that septal sheets are opposing adjacent sheets in the anterior and posterior wall. The opposite sign of the E2A between TOF and D-TGA may come from the difference of E2A in the septal bulging between TOF and D-TGA without VSD caused by the difference of ventricular pressure [ 39 ]. The difference of the E2A between myocardial segments may result from the hemodynamic change due to case-specific anatomic, vascular and post-surgical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that septal sheets are opposing adjacent sheets in the anterior and posterior wall. The opposite sign of the E2A between TOF and D-TGA may come from the difference of E2A in the septal bulging between TOF and D-TGA without VSD caused by the difference of ventricular pressure [ 39 ]. The difference of the E2A between myocardial segments may result from the hemodynamic change due to case-specific anatomic, vascular and post-surgical characteristics.…”
Section: Discussionmentioning
confidence: 99%